(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Thumb injuries constitute a challenge for the plastic surgeon because the loss of its function compromises the function of the entire upper limb. If there is a soft tissue defect in thumb where tendons, joints, or bones is exposed, it requires stable vascularized flap reconstruction preferably with a local or regional flap. The First Dorsal Metacarpal Artery (FDMA) island flap from the dorsum of the index finger is an option for reconstructing such thumb defect. Objectives: To assess the quality of sensitivity at flap site following reconstruction of soft tissue defect in thumb with the FDMA island flap. Materials and Methods: A prospective observational study was conducted from July 2012 to June 2013 among 31 patients admitted with soft tissue defect of thumb with exposure of tendon, bone, joint or loss of pulp and were treated with innervated FDMA island flap. Recovery of sensation was evaluated by static-2PD test. Results: Out of 31 patients 28 were male and 3 were female with male to female ratio is 9:1. The mean age was 26.2±8.8 years. A large number of patient was manual worker (construction worker, mechanic). Most of them sustained injury in their dominant thumb (61%). Most common cause of injury was electric burn (78%) rest were due to machinery injury. Average s-2PD over the flap area 9.1 mm (range, 8-12 mm) compared with 7.4 mm (range, 7-11 mm) over the donor site of opposite index finger and 5.5 mm (range, 3-9 mm) over corresponding site of opposite thumb. Average loss of s-2PD over the flap area compared with the donor area was 1.4 mm (19.2%). Every patient was satisfied with the outcome. Conclusion: Restoration of sensibility is quite satisfactory after reconstruction of soft tissue defect of thumb by first dorsal metacarpal artery island flap. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 34-38